Peran Kelompok Tani Terhadap Produksi Durian di Desa Kaligono Kecamatan Kaligesing Kabupaten Purworejo - Dwi Indah Suryani Pandan Arum; Arta Kusumaningrum; Isna Windani (Jurnal Riset Agribisnis dan Peternakan, 2019)
This study aims to: (1) Determine the role of farmer groups on durian production in Kaligono village, Kaligesing sub-district, Purworejo district. (2) Determine the relationship of the role of farmer groups to durian production in Kaligono village, Kaligesing sub-district, Purworejo district. The research design used in the study is a survey method. The study population of all durian farmers who are members of farmer groups in the village of Kaligono, Kaligesing district, Purworejo district, amounting to 262 farmers. The sample of respondents studied was 73 durian farmers determined using the Simple Random Sampling method. Data collection instruments using questionnaires, analysis using Likert scale, and Rank Spearman. The results showed that based on the results of the analysis using the Likert scale, the overall role of farmer groups in durian production obtained an average score of 25.58, which means it was included in the medium category, where the role of each farmer group in durian production was the role of farmer groups as learning units and cooperation units fall into the medium category with percentages of 35% and 37%, while the role of farmer groups as production units falls into the low category with a percentage of 28%. The results of the analysis with Rank Spearman, it is known that there is a significant relationship between the role of farmer groups as a unit of cooperation with the close relationship that is quite strong and there is no significant relationship between the role of farmer groups as learning units and production units.